Decentralization and the Social Economics of Development: Lessons from Kenya - Barrett, Christopher B (CABI, 2014)
The chapters of this volume represent a significant output of the Strategies and Analysis for Growth and Access (SAGA) project, a USAID-funded cooperative agreement directed by Cornell and Clark Atlanta Universities. SAGA brings together policy makers, researchers and other experts with an interest in African development. SAGA’s goals are to conduct high-quality, policy- relevant research, and to increase African capacity to produce such research on key issues affecting economic growth and welfare in Africa. While SAGA’s geographical coverage spans several countries in western, southern and eastern Africa and its research cuts across issues of health, education, vulnerability and empowerment, this book highlights the insights generated from research carried out by a range of collaborators in Kenya. Specifically, this volume collects research looking into the effect that decentralization, in its various forms, plays in stimulating rural development, empowering individuals and groups, and improving rural well-being. The institutional correlates of successful and unsuccessful decentralization efforts are also studied. The volume could not have reached fruition were it not for the dedication and contribution of the authors and co-authors of the chapters included herein. We extend our deep gratitude and appreciation for their hard work and commitment to this endeavour. Several other SAGA–Kenya researchers produced rigorous and insightful research around the parallel theme of ‘reducing risk in rural Kenya’. They too were valued members of the SAGA–Kenya team. We are indebted to them and sincerely thank and recognize Joseph Karugia, Paswel Marenya, Hezron Nyangito, Rose Nyikal, Walter Odhiambo and Willis Oluoch-Kosura for their efforts.